2016
DOI: 10.1038/srep21328
|View full text |Cite
|
Sign up to set email alerts
|

CMKLR1 deficiency maintains ovarian steroid production in mice treated chronically with dihydrotestosterone

Abstract: Elevated serum chemerin levels correlate with increased severity of polycystic ovary syndrome (PCOS). However, the role of CMKLR1 signaling in ovarian biology under conditions of excess DHT remains unclear. In this study we compared the effects of continuous 90-day high dose DHT exposure (83.3 □g/day) on wild type and CMKLR1-deficient mice. DHT induced PCOS-like clinical signs in wild type mice as well as significant changes in the expression of hormone receptors, steroid synthesis enzymes, and BMPs and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Chemerin expression is also increased in the ovaries of rats treated with 5alpha-dehydrotestosterone (DHT) (mimicking PCOS) that is associated with a decrease in oestradiol secretion in granulosa cells and induces apoptosis [ 210 ]. In mice with CMKLR1 gene deletions, the effects of chronic DHT treatment on ovarian function in experimental PCOS are largely reduced, suggesting a role of the chemerin system in PCOS pathology [ 211 ]. As already mentioned, PCOS syndrome is, in some cases, associated with insulin resistance, which can both be treated with antidiabetic drugs.…”
Section: Chemerinmentioning
confidence: 99%
“…Chemerin expression is also increased in the ovaries of rats treated with 5alpha-dehydrotestosterone (DHT) (mimicking PCOS) that is associated with a decrease in oestradiol secretion in granulosa cells and induces apoptosis [ 210 ]. In mice with CMKLR1 gene deletions, the effects of chronic DHT treatment on ovarian function in experimental PCOS are largely reduced, suggesting a role of the chemerin system in PCOS pathology [ 211 ]. As already mentioned, PCOS syndrome is, in some cases, associated with insulin resistance, which can both be treated with antidiabetic drugs.…”
Section: Chemerinmentioning
confidence: 99%
“…CMKLR1 is the most well-characterized Chemerin receptor, and most of the biological functions of Chemerin have been shown to depend on CMKLR1 activation [ 28 ]. Our recent study showed that CMKLR1 gene deletion attenuates the effects of chronic DHT treatment on ovarian function in experimental PCOS [ 29 ]. Although Chemerin is the only known ligand for GPR1, few functions have been suggested for GPR1.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic and abnormally high androgen levels suppress antral follicular development 39 . It has been previously demonstrated that androgen resulted in suppressed antral follicular growth and estrogen secretion in the rats and mice 26 , 40 , 41 . In addition, testosterone or DHT supplementation in pig oocytes cultures medium significantly increased the proportion of oocytes arrested in the metaphase I stage 42 .…”
Section: Discussionmentioning
confidence: 98%